Who switches and why? A diagnostic survey of retail financial services in Ireland - Féidhlim McGowan; Alexandros *1936-2023* Papadopulos; Pete Lunn (The Economic and Social Research Institute (ESRI), 2023)
Failure to switch service provider is viewed as leaving money on the table. While psychological hassle and switching costs are often invoked to explain the observed inertia, there is little empirical research that directly measures barriers to switching in retail finance markets. This study uses a large diagnostic survey (n = 2,903) to model predictors of switching for four retail financial products: bank current accounts, mortgages, loans, and credit cards. The survey gathers detailed individual histories of experience with original purchase and comparison decisions in each market, as well as search and switching activity for each product. In addition to standard socio-demographic factors, we measure psychological factors such as estimated savings from switching and perceived price dispersion in the market. We also record measures of financial literacy. Comparing offers when originally choosing a product emerges as a powerful predictor of later switching behaviour. This variable has considerably more explanatory power than financial literacy or socio-demographic background characteristics. Estimated savings is also a positive predictor of switching. Estimates of price dispersion are not reliably associated with switching outcomes. These findings, taken in aggregate, suggest that confidence in engaging with financial providers and products, and developing the habit of doing so from an early point, may be more important than comprehension of financial concepts, which is the typical policy route to consumer empowerment.
Keywords: C91; 330; barriers to switching; online survey; consumer preferences; switching costs